Leadership And Management Skills: A Neglected Issue in South African Municipalities - Sebola, Mokoko Piet (Jurnal Administrasi Publik (Public Administration Journal), 2025)
This paper aims to analyze the prevalence of ignorance of the significance of effective leadership and Management within the municipal administration setup. Such practice compromises service delivery at the coal face of the community. Service delivery has been and is still a problem in South African municipalities. Numerous concerns about it were raised, both scholarly and political. Leadership and Management are critical variables that have not been thoroughly investigated regarding their impact on impediments to municipal service delivery. The paper adopts a qualitative approach and employs a desktop study method to collect data that supports the notion that the South African political leadership is unaware of the importance of leadership and management skills in delivering services to the people. The results of the paper demonstrated that ignoring consideration of people’s leadership and management skills within the municipal environment leads to inefficient service delivery, a lack of public trust, corruption, public protests, and instability. The paper concludes that the consideration of leadership and management skills in the leadership and Management of South African municipalities can ensure the country's success in delivering services in its municipalities.